การพัฒนารูปแบบการสอนงานในการปฏิบัติการพยาบาลของพยาบาลพี่เลี้ยง โรงพยาบาลกรุงเทพขอนแก่น - จันทชุม วรรณชนก; ดาผา สมปรารถนา; ศรีตระกูล รัชตวรรณ; วงศ์สุดตา เหรียญทอง; คัทสิงห์ สุรวดี; กระแสร์ ศุภลักษณ์; ศรีสมบูรณ์ ดรุณี (วารสารการพยาบาลและการดูแลสุขภาพ, 2020)
This action research was to develop a coaching model of nursing practices among preceptors and assess its effectiveness on novice nurses’ performance scores. The participants of 9 nurse preceptors and 17 novice nurses were recruited from IPD wards at Bangkok Hospital Khon Kaen. The process was divided into 3 phases. The preparation phase was to identify problems and review literatures. The implementation phase was to develop the coaching program based on learning theory and proceed on the repeated coaching cycles for 8 weeks to reach the goals. The final phase was to compare novice nurses’ performance scores before and after model implementation. The research tool was a 12-item performance evaluation form of a 5-point scale. The content validity was explored by experts and Cronbach’s alpha coefficient was .98 for its reliability. Data were analyzed by frequency, percentage, average, standard deviation and t-test. The results were as follows: The developed coaching model was a combined coaching-learning which consisted of 4 stages in nursing practices: 1) exploration of novice nurses’ problems and needs, 2) setting goals and creating plans of action, 3) implementation of actions and 4) monitoring and evaluation of learning outcomes, which was facilitated through processes such as a powerful questioning, active listening, and providing constructive feedback. The novice nurses’ performance scores after model implementation were statistically significant higher than the previous session at the level of 0.05. (